Tourism in multicultural regions (on the example of the Ukrainian Danube) - Todorov, Vyacheslav; Khomutov, Victor (Journal of Danubian Studies and Research, 2023)
The Ukrainian Danube region is characterized by a high level of self-regulation of interethnic issues. In the two hundred years since the last colonization of the region, there have been no ethnic conflicts. The conflicts that did take place were purely domestic in nature. Socio-cultural boundary of the region, which is caused by centuries-old historical and geographical processes in the Northern Black Sea region, is a direct catalyst for modern geopolitical and geoeconomic changes. The relations between Ukraine and Romania have the greatest influence on these processes. With the beginning of the intensive phase of Russian aggression, the geopolitical position of the Ukrainian Danube region has changed significantly. This region became the main center of export-import operations of our state. After the end of the war, a flow of goods and people will go through the Ukrainian Danube region to restore public life. In such a situation, it is necessary to develop comprehensive plans for sustainable development of the region, which will take into account all its competitive advantages. It is of particular importance to use the multiculturalism of the region for the development of tourism and obtaining working capital for economic entities and territorial communities. The main attention should be paid to the ethnic tourism oriented to the citizens of the countries that have their diasporas in the south-western part of the Odessa region.